HUBUNGAN ANTARA BUDAYA ORGANISASI DAN KOMPETENSI PEDAGOGIK DENGAN KEINOVATIFAN GURU - Rita Marliana; Yossa Istiadi; Eka Suhardi (Universitas Pakuan, 2018)
The objective of this research is to analyse the correlation between organizational culture and pedagogic competence with innovation of civil servant teachers. The design of this study was survey and correlational approach. The research applies survey method to collect the data and correlational approach, the research that is designed to get the information about the correlation between variabel in the population. The population in this research is all civil servant teachers in state elementary school se-gugus 6 Pancoranmas district, Depok city totally 120 teachers. This research applied proportional random sampling design which determine a sample taken from a representative of each of the existing schools in the population whose numbers were adjusted by the amount of each allocation formula, using proportional random sampling using the formula with the total sample slovin as many as 93 teachers. The research revealed that there is positive and highly significant relationship between the organizational culture with teachers innovation. There are positive and highly significant relationship between pedagogic competence and teachers innovation.Keywords: Organizational Culture, Paedagogic Competence, Innovation